User-Generated Content and Its Impact on Purchase Intent for Tourism Products: A Comparative Analysis of Millennials and Centennials on TikTok - Eva Correia Ramos; Célia M. Q. Ramos (Future Internet)
In an increasingly technological society, online social networks are essential to support consumer purchasing decisions, primarily through User Generated Content (UGC). In this research, we look at the influence of UGC on purchase intent applied to the tourism product on the TikTok social network. In this sense, a survey was applied to TikTok users aged between 18 and 42 to compare their behaviour with that of the two generations: Millennials and Centennials. The results indicate a relationship of influence between credibility and the usefulness of information and between usefulness and social influence on the intention to buy tourism products and services. In addition, a comparison was made between the results of the sample of individuals belonging to the Millennial Generation and the sample of individuals belonging to the Centennial Generation, with the main discrepancy in the results being the relationship between the need for information and the usefulness of information. These insights pave the way for further research aimed at establishing more robust conclusions in this area.